2016
DOI: 10.3928/02793695-20151109-03
|View full text |Cite
|
Sign up to set email alerts
|

How Exercise Influences Cognitive Performance When Mild Cognitive Impairment Exists: A Literature Review

Abstract: Older adults who present with mild cognitive impairment (MCI) have an increased risk of developing more advanced dementia. However, no pharmacological treatment currently exists to slow the progression of or reverse MCI. The purpose of the current systematic review is to summarize evidence surrounding the impact of exercise interventions on the cognitive performance levels of community-dwelling older adults with MCI. Computerized database and ancestry search strategies located distinct intervention trials betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“… Buschert et al ( 2011 ) RCT, single-blind, active control n = 43 aMCI n = 27 mild AD n = 16 Tx n = 10 Cntl n = 12 Age: =71.2 s = 7.0 • 11 session minimum - 20 “units”, 120 min/ week • Group-based, multicomponent cognitive intervention including memory, cognitive stimulation, face-name association, errorless learning, principles of meta-cognition, education ADAS-cog, MMSE, TMT B, RBANS, story recall, MADRS, QoL-AD • Significant interaction between treatment and progression for ADAS-Cog (F = 6.2, p = 0.02, η2 = 0.26), MMSE (F = 3.8, p = 0.07, η2 = 0.17), RBANS story memory (F = 3.4, p = 0.08, η2 = 0.16) and TMT = B (F = 3.5, p = 0.08, η2 = 0.16) • Main effects for treatment were found for MMSE (F = 8.5, p < 0.01, η2 = .23), RBANS story memory (F = 12.5, p < 0.01, η2 = 0.41) and RBANS Story recall (F = 9.9, p < 0.01, η2 = 0.36) • ↑ in global cog status, and specific cog and non-cog functions • aMCI demonstrate significant change in ADAS-Cog scores • aMCI subjects demonstrated tendency toward higher attentional skills demonstrated by TMT-B • No significant effect on memory performance compared to active controls 0.661 5. Carretti et al ( 2013 ) RCT, active control n = 20 (aMCI) Tx n = 10 Cntl n = 10 Age: Tx: = 71.8 s = 2.20 Cntl: = 70.6 s = 2.63 • 5, 90 min sessions • Individual-based, one-on-one sessions using restorative strategies which focused on working memory techniques NPE, Vocab, CWMS, DS-FWD; DS-BWD, Dot matrix, List recall, Pattern comparison, Cattell test • Significant effect post training in CWMS (3.8), Dot Matrix (2.3), Cattell test (0.50) vs control CWMS (0.60), Dot Matrix (2.3), Cattell test (−0.40). P -values for these tests where groups improved by 1 SD are <0.01, <0.05, and <0.05, respectively • Verbal working memory training is a promising approach to sustaining memory function in aMCI • Working memory training showed transfer to some cognitive components of memory part of the core cognitive impairments responsible for MCI → AD −0.713 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Buschert et al ( 2011 ) RCT, single-blind, active control n = 43 aMCI n = 27 mild AD n = 16 Tx n = 10 Cntl n = 12 Age: =71.2 s = 7.0 • 11 session minimum - 20 “units”, 120 min/ week • Group-based, multicomponent cognitive intervention including memory, cognitive stimulation, face-name association, errorless learning, principles of meta-cognition, education ADAS-cog, MMSE, TMT B, RBANS, story recall, MADRS, QoL-AD • Significant interaction between treatment and progression for ADAS-Cog (F = 6.2, p = 0.02, η2 = 0.26), MMSE (F = 3.8, p = 0.07, η2 = 0.17), RBANS story memory (F = 3.4, p = 0.08, η2 = 0.16) and TMT = B (F = 3.5, p = 0.08, η2 = 0.16) • Main effects for treatment were found for MMSE (F = 8.5, p < 0.01, η2 = .23), RBANS story memory (F = 12.5, p < 0.01, η2 = 0.41) and RBANS Story recall (F = 9.9, p < 0.01, η2 = 0.36) • ↑ in global cog status, and specific cog and non-cog functions • aMCI demonstrate significant change in ADAS-Cog scores • aMCI subjects demonstrated tendency toward higher attentional skills demonstrated by TMT-B • No significant effect on memory performance compared to active controls 0.661 5. Carretti et al ( 2013 ) RCT, active control n = 20 (aMCI) Tx n = 10 Cntl n = 10 Age: Tx: = 71.8 s = 2.20 Cntl: = 70.6 s = 2.63 • 5, 90 min sessions • Individual-based, one-on-one sessions using restorative strategies which focused on working memory techniques NPE, Vocab, CWMS, DS-FWD; DS-BWD, Dot matrix, List recall, Pattern comparison, Cattell test • Significant effect post training in CWMS (3.8), Dot Matrix (2.3), Cattell test (0.50) vs control CWMS (0.60), Dot Matrix (2.3), Cattell test (−0.40). P -values for these tests where groups improved by 1 SD are <0.01, <0.05, and <0.05, respectively • Verbal working memory training is a promising approach to sustaining memory function in aMCI • Working memory training showed transfer to some cognitive components of memory part of the core cognitive impairments responsible for MCI → AD −0.713 6.…”
Section: Resultsmentioning
confidence: 99%
“…Test for heterogeneity Q = 205.409, df = 25; p = 0.000; I 2 = 87.829; τ 2 = 0.484 Intervention Effects – By Cognitive Domain : Please see Table 3 for a breakdown by domain including the study, outcome measures, effect sizes, indices of heterogeneity, and prediction intervals. Table 3 Effect sizes by cognitive domain: Effects of outcome measures, confidence intervals and prediction intervals Cognitive domain Study Measure n g Actual/ observed intervals p Q df ( Q ) p I 2 τ 2 τ Prediction intervals Lower (95%) Upper (95%) Lower (95%) Upper (95%) Mental status/ general cognitive Barban et al ( 2016 ) MMSE 106 0.111 −0.271 0.493 0.569 Barnes et al ( 2009 ) RBANS Total 36 0.374 −0.272 1.020 0.256 Buschert et al ( 2011 ) Combined (MMSE + ADAS-Cog) 22 0.387 −0.514 1.288 0.400 Carretti et al ( 2013 ) Cattell – CFT 20 0.818 −0.059 1.695 0.068 ...
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AAN recommends that exercise training and cognitive training may help to improve cognitive measures . Studies suggest that nonpharmacological interventions such as physical exercise, playing musical instruments, dance, Tai‐chi, computerized cognitive training and cognition‐based intervention, enhance global cognitive function, attention, executive function, processing speed, and delayed memory …”
Section: Implications For Nursing Practice and Researchmentioning
confidence: 99%
“… 2 Therefore, recent studies have focused on multiple non-pharmacological strategies to mitigate the progression to dementia in patients with MCI, including cognitive intervention or lifestyle changes (i.e., exercise). 3 4 …”
Section: Introductionmentioning
confidence: 99%